(untitled) - Dillon, Edward (London, 1906)
Chap I. Prehistoric Art, II. The Nara and Fujiwara, III, The Kamakura and Ashikaga Periods, IV. Hideyoshi and the Tokugawa Shoguns,...
Keywords: Mỹ thuật, Nhật bản,Arts, Japanese